Ross syndrome: A case report and review of cases from India - Manoj Kumar Agarwala; Leni George; Harshad Parmar; Vivek Mathew (Wolters Kluwer Medknow Publications, 2016)
Ross syndrome is a rare dysautonomia characterized by a clinical complex of segmental anhidrosis or hypohidrosis, areflexia, and tonic pupils. A very few cases (≃50) have been reported in literature since its original description in 1958. Here, we report the case of a middle-aged homemaker from Odisha, India, who presented with complaints of segmental hypohidrosis for the past 7 years.